CHUKWUMA NZEOGWU IN THE THROES OF CONTEMPORARY NIGERIAN HISTORY - Wambu, Chiemela; Ecoma, Chinyere (Advances in Social Sciences Research Journal, 2020)
For the greater part of its existence as a sovereign state, Nigeria has witnessed more years of military than civilian rule. An excursion into this very important aspect of our national history must, of necessity, interrogate the circumstances and dramatis personae that led to the military’s intervention in national politics. One name that has never escaped the scrutiny in this effort is that of Major Chukwuma Kaduna Nzeogwu. Though a posthumous research, the intention of this paper is to attempt a reappraisal of the often ignored, misinterpreted and maligned intentions of the principal actors of the January 15, 1966 military coup d’etat, especially the role of Nzeogwu. In order to achieve this objective, the research made use of both primary and secondary sources of data. These were subjected to initial qualitative analysis. The research concludes that part of the reasons for the misinterpretation of Nzeogwu’s role is the need to justify the failure of the government of the First Republic to satisfy the basic human and material needs of Nigeria. In addition, it establishes the fact that subsequent political equations and configurations in Nigeria have evidently been to the benefit of those who have been at pains to justify the brutality that attended the January 1966 coup d’etat.